T-junction Configuration Performance in aTransmission Sub-system - Fahmi Hakim, Muhammad; Hermawan, Ahmad; Ridzki, Imron; Setya Wiwaha, Sigit; Azizah Nurjannah Hamka Putri, Gadis (International Journal of Frontier Technology and Engineering, 2022)
A cement factory, namely PT Semen Imasco Asiatic, requires a large supply of power for production. However, in the area where the cement factory was established, namely Puger District, there was no electricity capable of supplying it, so PLN built the Puger substation. In the original plan, the transmission line will be built directly from GI Tanggul to GI Puger. However, because the plant must operate immediately, the electricity supply is taken from the existing Tanggul substation-Jember substation transmission line using the T-Junction configuration. In this paper, an analysis of the power flow of the Paiton-Grati subsystem will be carried out when the power supply from Tanggul Substation to Puger Substation is passed through the T-Junction configuration or when the transmission line is connected from the Tanggul Substation to the Puger Substation directly. The result of this research is that there is no significant difference between the two conditions in power losses, voltage drop, current, and power factor parameter so that the T-Junction configuration is quite feasible to use even though it is temporary.